Spontaneous rupture of umbilical hernia in an adult with evisceration of small bowel: a case report - Limbu, Yugal; Pokhrel, Manish; Bohara, Tanka Prasad; Joshi, Mukund Raj (Journal of Society of Surgeons of Nepal, 2020)
Spontaneous rupture of umbilical hernia in an adult patient is a rare presentation. We present a case of a 43-year old male patient with long standing history of umbilical hernia who presented with sudden spontaneous rupture of the hernia with evisceration of the small bowel. The authors would like to highlight this rare complication of umbilical hernia and its management.